2012
DOI: 10.1136/tobaccocontrol-2012-050529
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette butt littering in city streets: a new methodology for studying and results: Table 1

Abstract: Butt littering behaviour appears to be the norm among smokers in this urban setting, even though rubbish bins were ubiquitous. One solution is stronger enforcement of littering laws. Nevertheless, in a society with a national smokefree goal (by year 2025 for New Zealand), it would probably be more logical and cost effective to move to smokefree policies for major city streets, which are used in a number of jurisdictions internationally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 8 publications
2
37
0
Order By: Relevance
“…We next compared ROS reactivity in two different brands of used conventional cigarette filters (Moerman and Potts, 2011; Novotny et al, 2009; Novotny and Zhao, 1999; Patel et al, 2013; Pryor et al, 1998). As expected, ROS from smoked cigarette filters/butts produced a significant increase in DCF fluorescence for research grade reference cigarette (3R4F) and a significant increase in DCF fluorescence for Marlboro 100s (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next compared ROS reactivity in two different brands of used conventional cigarette filters (Moerman and Potts, 2011; Novotny et al, 2009; Novotny and Zhao, 1999; Patel et al, 2013; Pryor et al, 1998). As expected, ROS from smoked cigarette filters/butts produced a significant increase in DCF fluorescence for research grade reference cigarette (3R4F) and a significant increase in DCF fluorescence for Marlboro 100s (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since smoked cigarette filters are one of the most littered and frequently disposed forms of polluted consumer waste (Moerman and Potts, 2011; Novotny et al, 2009; Novotny and Zhao, 1999; Patel et al, 2013), we compared the reactivity of the e-cigarette cartomizer to used cigarette filters/butts. Cigarette tar, which collects in the filters, is known to contain stable oxidants/ROS that can liberate highly reactive forms of ROS after the tar is immersed into an aqueous solution (Pryor et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by the reluctance of industry to publish or provide methodological details15 27 on EPSs. Finally, as littering is illegal in many jurisdictions,71 72 it could be hypothesised that those that litter may be more likely to engage in other illegal activity, including use of illicit product, and thus that the EPSs may overestimate illicit. Investigator : In some countries (Austria, Belgium, Luxembourg), the national manufacturers’ associations (NMAs) carried out the surveys. As NMAs, like the companies they represent, have an interest in overestimating the extent of both illicit trade and counterfeit versus transnational tobacco company (TTC) illicit product, this represents a conflict of interest.…”
Section: A Review Of the Ps Methodologymentioning
confidence: 99%
“…This is supported by the reluctance of industry to publish or provide methodological details15 27 on EPSs. Finally, as littering is illegal in many jurisdictions,71 72 it could be hypothesised that those that litter may be more likely to engage in other illegal activity, including use of illicit product, and thus that the EPSs may overestimate illicit.…”
Section: A Review Of the Ps Methodologymentioning
confidence: 99%
“…The American Legacy Foundation surveyed a national sample of 1000 smokers and found that most (74.1 %) admitted disposing of butts on the ground or out of a car window at least once in their lives [9]. Recent observational studies of smokers document that a majority (76.7 %; 95 % CI 70.8–82.0 %) of 219 subjects littered their cigarette butts; this behavior appears to be the norm among smokers in urban settings, even in the presence of appropriate waste receptacles [10]. …”
Section: Introductionmentioning
confidence: 99%